The Implementation of Non-Sequential Strategy to Face TOEFL ITP Problems - Ahmad Tauchid; Edi Suwandi (Journal of English Language Learning, 2021)
TOEFL was seen as a prerequisite for non-native English students to study abroad, to get a suitable employment, and to get a university diploma. Students also found it challenging to complete the TOEFL reading exam. This was an experimental research based on applying a non-sequential strategy. This study aimed at investigating whether the use of non-sequential strategy was effective to complete the reading comprehension session in TOEFL ITP or not. 100 English university students engaged entirely in the study as participants. They were studying at Universitas Nahdlatul Ulama Sunan Giri (UNUGIRI) located in Bojonegoro, Eastern Java, Indonesia. The researcherss provided the students a pre-test and post-test in order to collect the data. The students were permitted to perform the exam on their own during the pre-test. In this pre-test the researcherss provided no special instructions. In the post-test, the participants got a preferential treatment. The students were advised to follow a non-sequential strategy for the exam. The data were produced through the students’ compilation of TOEFL scores. The data were anlyzed by comparing the students’ scores in pre-test and post-test. The results showed that a non-sequential strategy to complete the reading comprehension session of the TOEFL test is very effective to be implemented. This result is addressed further in this article.